If the sum of the first n terms of an AP is given by Sn=(3n²-n), find its nth term. About the author Bella

Given Sum of n terms is S n =3n 2 −4n So Sum of n−1 terms is S n−1 =3(n−1) 2 −4(n−1) =3n 2 −6n+3−4n+4 =3n 2 −10n+7 Sum of n terms is equal to sum of n−1 terms plus n th term ⟹n th term =S n −S n−1 =3n 2 −4n−(3n 2 −10n+7) n th term=6n−7 Reply

Answer: An(nth term) is given by Sn – Sn-1 =>An=3n²-n-3n²-3-n+1 =>An=-2-2n answerr hope it’s help you plss mark me brainliest!!! Reply

## Given Sum of n terms is S

## n

## =3n

## 2

## −4n

## So Sum of n−1 terms is S

## n−1

## =3(n−1)

## 2

## −4(n−1)

## =3n

## 2

## −6n+3−4n+4

## =3n

## 2

## −10n+7

## Sum of n terms is equal to sum of n−1 terms plus n

## th

## term

## ⟹n

## th

## term =S

## n

## −S

## n−1

## =3n

## 2

## −4n−(3n

## 2

## −10n+7)

## n

## th

## term=6n−7

Answer:An(nth term) is given by Sn – Sn-1

=>An=3n²-n-3n²-3-n+1

=>An=-2-2n answerr

hope it’s help you

plss mark me brainliest!!!